Evaluation of total phenolic contents and antioxidant activities in different solvent extracts of Diospyros melanoxylon Roxb. bark - Jaiwal, B V; Shaikh, F K; Waghire, H B; Sarwade, B P (Journal of Experimental Sciences, 2012)
Antibacterial and anticardidal activities from the polar and non-polar solvent extracts of Diospyros melanoxylon Roxb. is established earlier. Here we have evaluated amount of total phenolics present in Aqueous, Methanol, Ethanol, Acetone, Ethyl acetate, and Chloroform solvents by using Folin-ciocaltuaeu reagent from Diospyros melanoxylon Roxb. bark. Anti-oxidative potential of phenolics present in different solvents were evaluated by DPPH free radical scavenging assay, O-phenanthroline assay and reducing power assay. It was observed that the Methanol is a better solvent for the total phenolics extraction. The amount of phenolics present in solvents were in the order of Methanol > Ethanol > Acetone > Aqueous > Ethyl acetate. The highest free radical scavenging potential 59.33 ± 1.52% was observed in Ethanol extract and the lowest scavenging potential 39.66 ± 1.52% in Aqueous extract. The highest scavenging potential 66.66 ± 2.4% was observed in Acetone extract in case of O-phenanthroline assay. The similar scavenging potential was observed in Aqueous, Methanol, Ethanol and Acetone extracts in case of reducing power assay. This study shows that the Diospyros melanoxylon Roxb. bark extract could be used as probable antioxidative agent.